Production of Dextrin by Steam Explosion from Starch Extracted from Oil Palm Stem Waste - Yusra, Syarifah; Hidayat, Chusnul; Pranoto, Yudi; Anwar, Chairil; Damayanti, Rizki; Zulfajri, Muhammad; Saragih, Sri Wahyuna (Department of Science and Technology, 2022)
This research aimed to modify a starch obtained from palm oil production waste to produce dextrin through steam explosion (SE). The SE process was performed at different temperatures (120, 130, 140, 150, and 160 °C), and the physicochemical characteristics of the dextrin products – including the dextrin solubility, moisture content, and ash content – were analyzed. Besides, SEM image, XRD profile, FTIR profile, DSC profile, dextrose equivalent (DE) and molecular weights (MWs) were examined. The results showed that the SE process at 120 °C gave the best characteristics of dextrin, which was comparable to the commercial dextrin (CD). This dextrin had the best solubility among other products. The SEM image showed that the starch completely hydrolyzed into dextrin after SE treatment, and the dextrin crystal was mostly in irregular form. The XRD profile of the dextrin exhibited the same diffractogram patterns with a peak at 2-theta = 19.4. The FTIR profiles of the products exhibited main peaks at 1148, 1077, 994, and 928 cm–1, which were almost similar to the CD. The transition enthalpy (ΔH) of the dextrin (8.59 J/g) was greater than that of the CD (6.18 J/g), exhibiting a better hydrolysis process on the starch. Among the temperature treatments, the highest DE value was obtained for the SE treatment at 120 °C (10.33), which was still less than that of CD (18.46). The MW of the product was 102000 g/mol, which was higher than that of CD (44000 g/mol). © 2022, Department of Science and Technology. All rights reserved.